2019
DOI: 10.1186/s12871-019-0849-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics, risk factors, immune status and prognosis of secondary infection of sepsis: a retrospective observational study

Abstract: Background Secondary infection has a higher incidence in septic patients and affects clinical outcomes. This study aims to investigate the clinical characteristics, risk factors, immune status and prognosis of secondary infection of sepsis. Methods A four-year retrospective study was carried out in Zhongshan Hospital, Fudan University, enrolling septic patients admitted between January, 2014 and January, 2018. Clinical data were acqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…The risk factors for secondary infections include disease severity, shock, use of a central venous catheter, and mechanical ventilation. [1,6] However, we found an inverse association between disease severity and secondary infections. In a recent multicenter study, the rate of secondary pneumonia was higher in patients in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) group than in those in the infl uenza and no viral infection groups; however, simplified acute physiology score 2 and SOFA scores were lower in the SARS-CoV-2 group than in the other two groups.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The risk factors for secondary infections include disease severity, shock, use of a central venous catheter, and mechanical ventilation. [1,6] However, we found an inverse association between disease severity and secondary infections. In a recent multicenter study, the rate of secondary pneumonia was higher in patients in the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) group than in those in the infl uenza and no viral infection groups; however, simplified acute physiology score 2 and SOFA scores were lower in the SARS-CoV-2 group than in the other two groups.…”
Section: Discussioncontrasting
confidence: 46%
“…Secondary infections after admission to the ICU were reported to range from 13% to 29%. [1,6] No signifi cant diff erence in the rate of secondary infections was observed between septic and non-septic patients. In this study, the incidence of secondary infections was 8%, which was lower than that reported in previous studies, [1,6] which could be attributed to patients' mild status in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings were reported in those two previous large observational studies, which were 14.4% and 13.5%, respectively, although we recorded a slightly higher cumulative incidence of ICU-acquired infections ( van Vught et al., 2016 ; van Vught et al., 2017 ). Nevertheless, the higher observation was discovered in two retrospective studies, which were 31.0% and 38.9% ( Zhao et al., 2016 ; Chen et al., 2019 ). This may have been due to the relatively limited sample size and the definition of sepsis 2.0.…”
Section: Discussionmentioning
confidence: 75%
“…In patients with sepsis, this risk of developing ICU-acquired infection is influenced by multiple interrelated factors. For example, some studies from 10 years ago with small sample sizes or covering a short period of ( Chen et al., 2022 ) time showed that advanced age, disease severity, deep venous catheterization, and invasive ventilation were associated with an increased risk of incident ICU-acquired infection in sepsis ( Wolkewitz et al., 2014 ; van Vught et al., 2016 ; Chen et al., 2019 ). Despite associations of lower human leukocyte antigen expression and increased interleukin-10 (IL-10) levels with ICU-acquired infection ( van Vught et al., 2017 ; Stortz et al., 2018 ), identifying which patients are at a higher risk of sepsis-associated ICU-acquired infection remains clinically challenging.…”
Section: Introductionmentioning
confidence: 99%
“…We wished to consider also cases where the pathogen load is relatively low, yet persistent, which can, for example, lead to catastrophic outcomes, such as multiple organ failure (MOF), due to chronic inflammation ( 3 , 55 ). We included CTL suppression level, Z L , to represent the potency of the cellular immune system, and to reflect its ability to suppress secondary infections, which can frequently occur in an intensive care unit (ICU) setting ( 56 , 57 ). Additionally, Z L measures the efficacy of the drug in achieving its specific purpose of reinvigorating CTLs.…”
Section: Methodsmentioning
confidence: 99%